1981
DOI: 10.1007/bf00422121
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of brown adipose tissue in outdoor workers

Abstract: Histochemical reactions and activities of mitochondrial enzymes in adipose tissue around the neck arteries and in pericardium were studied in men who had been outdoor workers in northern Finland. The purpose was to study the occurrence of brown fat in workers having been exposed to cool or cold ambient temperature. Indoor workers of the same age were used as controls. Histochemically, no mitochondrial enzyme reactions were seen in the adipose tissues taken from the indoor workers, whereas some outdoor workers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
152
0
2

Year Published

1985
1985
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(158 citation statements)
references
References 15 publications
4
152
0
2
Order By: Relevance
“…In this regard, we note that the induction of thermogenic genes by cool temperatures is sufficient in isolated cells to increase both total respiration and the uncoupled fraction of respiration. Human studies have found that more brown fat and more active brown fat was present in individuals that were acutely exposed to cold (32), living in winter (4,32) or chronically working in the cold (33). Of course, the prevailing view has been that this was mainly a result of increased SNS activity as a consequence of cold.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, we note that the induction of thermogenic genes by cool temperatures is sufficient in isolated cells to increase both total respiration and the uncoupled fraction of respiration. Human studies have found that more brown fat and more active brown fat was present in individuals that were acutely exposed to cold (32), living in winter (4,32) or chronically working in the cold (33). Of course, the prevailing view has been that this was mainly a result of increased SNS activity as a consequence of cold.…”
Section: Discussionmentioning
confidence: 99%
“…However, brown fat -like adipocytes are found interspersed in WAT in both humans and rodents. As shown in Figure 2, the development of these cells is enhanced by b3-adrenergic stimulation, chronic activation of PPARg, or adaptation to cold response (Huttunen et al 1981;Cousin et al 1992;Ghorbani and HimmsHagen 1997;Guerra et al 1998;Himms-Hagen et al 2000;Xue et al 2005;Petrovic et al 2010). These brown fat-like cells present in WAT depots have been referred to as brite cells (brown in white), beige cells, adaptive brown fat cells, and recruitable brown fat cells (Enerback 2009;Ishibashi and Seale 2010;Petrovic et al 2010).…”
Section: The Cellular Origins Of Adipocytesmentioning
confidence: 99%
“…Apart from this, there is also evidence to show that the histological appearance of BAT in cadavers of outdoor workers (Finnish lumberjacks) shows evidence of greater activity than BAT taken from indoor workers, and this difference was greatest in those outdoor workers dying during the winter months. 15 In addition to cold-induced thermogenesis, another aspect of thermoregulation that helps explain the evolutionary persistence of thermogenesis is fever. Fever is produced by a combination of reduced heat loss (for example vasoconstriction) and increased heat production (both shivering and NST) in order to produce an elevation in the`set-point' temperature.…”
Section: Evolution Of Thermogenesismentioning
confidence: 99%